Remembering Msit No'kmaq: Self-in-Relation Métissage - Scott, Michelle Elizabeth (Graduate Studies, 2023)
In the spirit of relationship renewal and repair, I ask the question: How can we begin to enact our responsibilities to learn how to be good relatives to each other, the Land, and our other-than-human kin that is outside of the settler-colonial violence that Canada is built on? I suggest a necessary first step is to take our own self-reflective journey(s) of self-in-relation (Graveline, 1998) to locate our unique kinship networks of relationality and responsibility across time and space. In my research, I centred my embodied personal theory-making (Simpson, 2017), kinship relationality (Donald, 2021) and relationships to Land (Simpson, 2014, 2017; Styres, 2011, 2017, 2019) as a Mi’kmaw and Irish/English woman who has lived in Moh’kins’tsis for twenty-two years, was born and raised in Oniatari:io, and has ancestral and kinship ties to my Mi’kmaw relatives in Ktaqmkuk. Through the process of creating my métissage, I came to know and conceptualize colonial shrapnel as the ways in which colonial violence is embedded within our bodies through generations of spiritual, emotional, and blood and bone memory, and Elemental Kinship as a way to repair and heal through direct relationship with the elements – water, fire, earth, and air. I offer these concepts as curricular apertures with an invitation to others who are interested in moving beyond a fractured identity (personally, and collectively) toward a curriculum of remembering msit no’kmaq (all my [their] relations) at their own sacred fire.